2021
DOI: 10.1002/mp.15001
|View full text |Cite
|
Sign up to set email alerts
|

A clinical‐radiomics model incorporating T2‐weighted and diffusion‐weighted magnetic resonance images predicts the existence of lymphovascular invasion / perineural invasion in patients with colorectal cancer

Abstract: Purpose Lymphovascular invasion (LVI) and perineural invasion (PNI) are independent prognostic factors in patients with colorectal cancer (CRC). In this study, we aimed to develop and validate a preoperative predictive model based on high‐throughput radiomic features and clinical factors for accurate prediction of LVI/PNI in these patients. Methods Two hundred and sixty‐three patients who underwent colorectal resection for histologically confirmed CRC between 1 February 2011 and 30 June 2020 were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Second, the three-dimensional method can more accurately and fully characterize the voxel characteristics than the two-dimensional method, as shown in previous studies [ 26 , 27 ]. In recent years, there have been several studies similarly exploring the role of MRI based radiomics for LVI in patients with rectal cancer [ 28 , 29 ].But differently, we focused on those patients with negative statue of mrEMVI. As the previous evidence showed, MRI has high specificity but moderate sensitivity in the detection of EMVI.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the three-dimensional method can more accurately and fully characterize the voxel characteristics than the two-dimensional method, as shown in previous studies [ 26 , 27 ]. In recent years, there have been several studies similarly exploring the role of MRI based radiomics for LVI in patients with rectal cancer [ 28 , 29 ].But differently, we focused on those patients with negative statue of mrEMVI. As the previous evidence showed, MRI has high specificity but moderate sensitivity in the detection of EMVI.…”
Section: Discussionmentioning
confidence: 99%
“…When both systemic bone phenomena and CT cannot determine the existence of bone metastasis, mpMRI is usually feasible. Generally speaking, mpMRI includes conventional sequences (TIW1 and T2W1) and functional sequences (DWI, DCE-MRI and MRS) ( 38 , 39 ). Among them, DWI is more sensitive to monitoring bone metastasis of colorectal cancer than conventional sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the LR (AUC 0.866, 95%CI: 0.808-0.925) and extreme gradient boosting models (AUC 0.903, 95%CI: 0.855-0.951) performed the best, outperforming F-18-FDG-PET/CT on both the training set and the test set[ 85 ]. Other studies have also shown that radiomics has a good ability to predict metastasis to distant organs, such as the liver and lung, as well as vascular and perineural invasion[ 86 , 87 ]. It is reported that the predictive power of CT-based radiomics for the preoperative staging of CRC.…”
Section: Radiomics Workflowmentioning
confidence: 99%